TIGA DIMENSI DASAR RELASI MANUSIA DALAM KEHIDUPAN SOSIAL - Stimson Hutagalung (Fakultas Filsafat Universitas Advent Indonesia, 2015)
Early relationships in the life of humans as social beings generally begin inthree dimensions: family, marriage and friendship. The family is the corerelationships in the social institutions of mankind because families formedcommunity and nation. Marriage is a relationship that is the closest, most intimate inhuman relations area and the most ideal relationship among other relationship. Bibleuses the marital relationship to symbolized God's relationship with His people, Christas the bridegroom and his church as the bride. As social beings, friendship relation isa necessity. Friendship is a reciprocal relationship between individuals who each ofone will build relation one another.